If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 10 = 14x Reorder the terms: 10 + 12x = 14x Solving 10 + 12x = 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. 10 + 12x + -14x = 14x + -14x Combine like terms: 12x + -14x = -2x 10 + -2x = 14x + -14x Combine like terms: 14x + -14x = 0 10 + -2x = 0 Add '-10' to each side of the equation. 10 + -10 + -2x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -2x = 0 + -10 -2x = 0 + -10 Combine like terms: 0 + -10 = -10 -2x = -10 Divide each side by '-2'. x = 5 Simplifying x = 5
| -5(3-q)+4=5q | | 5(b+1)-6=2b-16 | | 8.364km= | | 1/3=4/6q | | 2y+3(0)y=10-0 | | 6m-2=-2-7m-m | | 15(x-3)=105 | | 3/4-3/4=0 | | -8(-2b+2)=-128 | | -8(1-4p)=120 | | 6t+3(5+-4)=12(2+-5) | | 6+2(33-x)-3+x= | | (25x)/45=-67 | | 2(5x-6)-3(1-x)=4-6(x+2) | | 5/7÷1/3 | | 12-3(4w-1)=7w-3(7+w) | | 2x+7-3x=6x-1 | | 6-2x-1=4x+6-6x-3 | | -(5b-1)=5b-(b-4) | | 7y^2-68y-20=0 | | -5-3(1-8p)=18-2p | | 2y-3x(x-8)=0 | | -103+2x=44-5x | | 232=-8(3x-5) | | 9x-9=18+6x | | 3+4y=15 | | 7-3r=r-(r+1) | | -2(3x-7)=36 | | 16+4x+3=-2x-(-6x)+12-(-7) | | 5x-100=-2x+40 | | 7x-4=-11x+6 | | 25x/45=-67 |